2010
DOI: 10.1258/jms.2010.009120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender, Age and Deprivation on Key Performance Indicators in a Fobt-based Colorectal Screening Programme

Abstract: a demonstration pilot of biennial guaiac faecal occult blood test (gFOBT) colorectal screening was carried out in North-East Scotland for all individuals aged 50 -69 years. Methods The relevant populations were subdivided, by gender, into four age groups and into five deprivation categories according to the Scottish Index of Multiple Deprivation (SIMD), and key performance indicators analysed within these groups. Results In all rounds, uptake of the gFOBT increased with age (P , 0.001), decreased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
92
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 27 publications
14
92
1
1
Order By: Relevance
“…Completion rates of a second FOBt following a false positive has been recorded at 69.6% [56] which is below the 85.4% completion rate of a second test among all first time completers (regardless of their screening result in the first round of screening) [36], suggesting lower participation in repeat screening in this group. However, such figures do not control for any other differences between the two groups in terms of demographic variables, such as gender and SES, which also affect uptake [57,58] and further research should establish whether FP results adversely affect future screening uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Completion rates of a second FOBt following a false positive has been recorded at 69.6% [56] which is below the 85.4% completion rate of a second test among all first time completers (regardless of their screening result in the first round of screening) [36], suggesting lower participation in repeat screening in this group. However, such figures do not control for any other differences between the two groups in terms of demographic variables, such as gender and SES, which also affect uptake [57,58] and further research should establish whether FP results adversely affect future screening uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The number needed to screen (NNscreen) was calculated as the number of complete screening tests needed to find one advanced neoplasia or CRC. All test characteristics were calculated separately for cut-off levels of 10,15,20,25,30,35, and 40 mg Hb/g feces, respectively. FIT test characteristics and FIT concentrations were adjusted for age via logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, guaiac-based FOBT screening results in a lower positivity and detection rate and may result in a higher proportion of false-positive test results in women. [14][15][16] A Scottish guaiac-based (gFOBT) screening study reported more screen-detected CRCs in men (64.5%) compared with women (35.5%), whereas the number of interval CRCs was similar in both groups (men, 49.8%; women, 50.2%). 17 These data suggest that gFOBT is less sensitive when used in women.…”
mentioning
confidence: 99%
“…It is well documented that uptake using gFOBT is lower in men than in women, increases with age, and is lower in the most deprived. 13,14 Thus, an aspiration of any bowel screening programme would be to find methods to increase uptake, particularly in men, the young and the deprived. We therefore investigated whether the overall increased uptake we found with FIT as a first-line test was achieving this aim, by comparison with a group from nine NHS Boards for whom we had detailed information on age, sex and deprivation.…”
Section: Introductionmentioning
confidence: 99%